The Effect of HER2 Status on Metaplastic Breast Cancer A Propensity Score-Matched Analysis - Hu, Jin; Zhang, Yanting; Dong, Fang; Shen, Jian; Chen, Hengyu; Li, Lei; Huang, Tao (Frontiers in Endocrinology, 2022)
Background: The role of human epidermal growth factor receptor 2 (HER2) in metaplastic breast cancer (MBC) patients remains unclear. The present study aimed to evaluate the effect of HER2 status on MBC patients by propensity-score matching (PSM). Methods: The SEER data from 2010 to 2016 were extracted. The breast cancer-specific survival (BCSS) of MBC patients, diagnosed from 2001 to 2016, was compared using Kaplan–Meier analysis. The multivariate Cox proportional model between groups was performed. PSM was used to make 1:1 case-control matching. Results: We included 1887 patients with a median follow-up time of 28 months (range 1-83 months). 1749 (92.7%) and 138 (7.3%) patients presented in the HER2-negative group and HER2-positive group. 833 (44.1%) patients received post-mastectomy radiotherapy (PMRT). The HER2-positive group had younger patients, lower tumor grades, and more advanced tumor stages. The prognoses were related to age of diagnosis, race/ ethnicity, TNM stage, and PMRT in multivariate Cox analysis. ER status and HER2 status had no impact on BCSS. In the Kaplan-Meier analysis, PMRT was associated with a better prognosis. Importantly, patients with HER2-negative status can benefit from PMRT, but not those with HER2-positive status. After PSM, on multivariate Cox analysis, the prognosis was related to HER2 status and PMRT. In the Kaplan-Meier analysis, PMRT was related to a better prognosis for HER2-negative patients. Conclusions: Our findings supported that PMRT and HER2-positive status were associated with a better prognosis after PSM. However, HER2-negative, but not HER2-positive patients could benefit from PMRT.